2018
DOI: 10.5815/ijeme.2018.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Malay Language Mobile Learning System (MLMLS) using NFC Technology

Abstract: This paper proposes a portable learning framework that uses cell phones and Near Field Communication (NFC) innovation in which this application permits understudies to connect with genuine questions and get data from the labels that are put on the item by filtering the tag put on the article. These gimmicks empower the learning procedure at all over the place (pervasive learning) and enhance the viability of the learning methodology. In this paper, Mobile Application Development Lifecycle (MADLC) model was uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Several recent studies have been conducted aimed at investigating the adoption of e-government services [74][75][76][77]. Little consideration has been paid in terms of exploring the main factors that influence the adoption of smart-government services at the three main stages of smart-government service use (the static, interaction, and transaction stages).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have been conducted aimed at investigating the adoption of e-government services [74][75][76][77]. Little consideration has been paid in terms of exploring the main factors that influence the adoption of smart-government services at the three main stages of smart-government service use (the static, interaction, and transaction stages).…”
Section: Discussionmentioning
confidence: 99%
“…The first of these steps, traditionally employed by researchers to ensure the validity of the indicators in the model, is cross-loadings [56]. In this section, the cross-loadings of any factor should be the strongest in its area compared to the rest of the other factors for it to be valid [64]. All the factors tested in this study showed their strength in their respective regions, as shown in Table 3.…”
Section: Measurement Model Analysismentioning
confidence: 96%
“…Several researchers have confirmed that incorporating m-learning systems in higher education ultimately improves access to quality education [12][13][14]. Others have argued that introducing m-learning platforms in learning process provides innovative ways of learning that engage the modern day learner [15][16][17][18].…”
Section: Literature Review 21 Value Of M-learning Systems In Higher Education During Covid-19mentioning
confidence: 99%